PREVENTIVE EFFECT OF MALOTILATE ON ETHANOL INDUCED HEPATIC DYSFUNCTION IN RATS - KANCHAN DNYANESH BOROLE,; SUBHASH LAXMANRAO BODHANKAR, (International Journal of Pharma and Bio Sciences, 2014)
The liver damage of variable severity is well known in chronic alcoholics. There are no promising drugs available to prevent or treat the Alcohol Induced Liver Disease (ALD). Malotilate, a sulphur containing compound, was discovered in Japan, which shows hepatocyte regenerating activity by enhancement of RNA and protein synthesis in liver. The objective of the study was to evaluate hepatoprotective effect of malotilate on ALD in rats. Sprague Dawley rats were divided into 5 groups, and treated as: 1. Control: ethanol40% v/v (orally 1ml / 100 g Day), 2. Vehicle control: ethanol+ methyl cellulose and 3, 4, 5: ethanol+ malotilate, at three dose levels viz. 25 (Low), 50 (Moderate), 100 (High) mg/kg/day orally, respectively, for 21 days. The liver function was assessed biochemically on day -1 and day-21. The histopathological assessment was done on day-21. The results demonstrated that, ethanol induced significant hepatic dysfunction and structural damage. Malotilate showed hepatocyte protective effect in ALD in a dose dependent manner. This study indicated that malotilate prevented ALD in alcoholic rats. However, clinical studies are needed to establish the efficacy of Malotilate on ALD in chronic alcoholics.